2008
DOI: 10.1002/jsfa.3219
|View full text |Cite
|
Sign up to set email alerts
|

Structural and chemical differences in the cell wall regions in relation to scale firmness of three onion (Allium cepa L.) selections at harvest and during storage

Abstract: BACKGROUND: Firmness in vegetables is an important textural attribute affecting consumer attitudes toward freshness and quality. Firmness, structural carbohydrates, polygalacturonase (PG), and pectin methylesterase (PME) activity were measured in three onion (Allium cepa L.) lines at harvest and after 4, 8, and 12 weeks of storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Bulb firmness is correlated to mechanical harvest and storage ability of onion cultivars (Larsen et al, 2009). Studies have shown that high dry matter onions had the firmest bulbs at harvest and delayed softening during storage (Coolong et al, 2008). In the collection studied here, bulb firmness ranged from 3 to 9 kg cm -2 .…”
Section: Bulb Firmnessmentioning
confidence: 89%
See 1 more Smart Citation
“…Bulb firmness is correlated to mechanical harvest and storage ability of onion cultivars (Larsen et al, 2009). Studies have shown that high dry matter onions had the firmest bulbs at harvest and delayed softening during storage (Coolong et al, 2008). In the collection studied here, bulb firmness ranged from 3 to 9 kg cm -2 .…”
Section: Bulb Firmnessmentioning
confidence: 89%
“…Firmness in vegetables is an important textural attribute affecting consumer attitudes toward freshness and quality, which has been also studied in onions (Coolong et al, 2008). Bulb firmness is correlated to mechanical harvest and storage ability of onion cultivars (Larsen et al, 2009).…”
Section: Bulb Firmnessmentioning
confidence: 99%
“…A correlation of dry matter content with texture has been observed in onion and steam-cooked potato (Coolong et al, 2008;van Dijk et al, 2002). The firmness of onion bulbs at harvest correlated well with bulb dry matter content (Coolong et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…A correlation of dry matter content with texture has been observed in onion and steam-cooked potato (Coolong et al, 2008;van Dijk et al, 2002). The firmness of onion bulbs at harvest correlated well with bulb dry matter content (Coolong et al, 2008). In contrast, in steam-cooked potato, van Dijk et al (2002) observed that the regression coefficient of the dry matter content and firmness (mouthfeel) was negligible and they concluded that potatoes with high dry matter content are crumbly and grainy (mouthfeel).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of phenolic compounds with subsequent increase is possibly related to the biosynthesis of flavonoids, mainly quercetin. The non-structural sugars increase in onion bulbs during storage [42,43,44] to provide metabolic energy for flavonoid biosynthesis [45]. The increase in flavonoid content, especially quercetin, at the end of storage is related to formation and brown staining of onion peel [46], breakage of dormancy and budding [45].…”
Section: Fig 2 Phenolic Compounds (A) Acidity (B) and Enzymatic Acmentioning
confidence: 99%